2009
DOI: 10.1037/1948-1985.s.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Asian cultural values gap, cognitive flexibility, coping strategies, and parent-child conflicts among Korean Americans.

Abstract: The study examined Korean American college students' perceived Asian cultural values gap between themselves and their parents, cognitive flexibility, and coping strategies. The relationships between these factors were studied with the intensities and types of parent-child conflicts. The results indicated that the participants adhered less strongly to Asian values than their parents. When faced with conflicts, the participants reported using problem solving coping strategy to the greatest extent, followed by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…In contrast to evidence demonstrating that women experience intergenerational cultural conflict more frequently and are more negatively affected by this family conflict than men, some studies have shown nonsignificant gender differences. In research that focuses on overall levels of intergenerational cultural conflict, data show no gender differences in the frequency of the conflict (Ahn et al, 2008;Lee et al, 2005;Su et al, 2005) nor in the associations between intergenerational cultural conflict and psychological adjustment outcomes (Lui, 2019). Perhaps, gender similarities in global levels of intergenerational cultural conflict are observed because traditional gender role expectations do not differ in most areas of intergenerational cultural conflict, such as education and career.…”
Section: Gendermentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to evidence demonstrating that women experience intergenerational cultural conflict more frequently and are more negatively affected by this family conflict than men, some studies have shown nonsignificant gender differences. In research that focuses on overall levels of intergenerational cultural conflict, data show no gender differences in the frequency of the conflict (Ahn et al, 2008;Lee et al, 2005;Su et al, 2005) nor in the associations between intergenerational cultural conflict and psychological adjustment outcomes (Lui, 2019). Perhaps, gender similarities in global levels of intergenerational cultural conflict are observed because traditional gender role expectations do not differ in most areas of intergenerational cultural conflict, such as education and career.…”
Section: Gendermentioning
confidence: 95%
“…Considering differences in the rates and strategies by which individuals acculturate to the mainstream U.S. culture and enculturate to Asian ethnic societies, parents and offspring within the same family may show discrepant patterns of behavioral repertoires and cultural values. In terms of cultural values, parents and offspring typically disagree on traditional values that emphasize filial piety, academic achievement, parental authority, and a hierarchical structure within the family (Ahn et al, 2008;Tsai-Chae & Nagata, 2008). Parent-offspring acculturation mismatch can manifest in at least four profiles: the offspring may be more acculturated to the host society than the parent; the offspring may be less acculturated to the host society than the parent; the offspring may be more enculturated to the heritage society than the parent; and the offspring may be less enculturated to the heritage society than the parent (Telzer, 2010).…”
Section: Intergenerational Cultural Conflict and Psychological Adjustmentioning
confidence: 99%
“…Adolescents from collectivistic immigrant cultures are likely to hold differing dating beliefs than are their parents, specifically regarding dating outside of one's group (Giguere, Lalonde, & Lou, 2010). Among U.S. Asian families, these intercultural discrepancies on values, which can manifest in attitudinal differences on topics such as dating, are associated with parent-adolescent conflict (Ahn et al, 2009). If parent-adolescent conflict is linked to differences in dating attitudes, it could be expected that parent-adolescent closeness is linked to adolescents feeling more receptive to expectations of dating within one's ethnicity.…”
Section: Correlates Of Dating Preferences: the Role Of Family And Socmentioning
confidence: 99%
“…Cognitive flexibility is defined as a person's awareness and capacity to consider alternatives when experiencing conflicts (Martin & Rubin, ). Research suggests that cognitive flexibility is associated with effectively managing cultural differences (Ahn, Kim, & Park, ). Openness to experience—that is, individuals' acceptance of new stimuli and willingness to adjust their attitudes—has been associated with more sensitivity in interacting with people different from oneself (Flynn, ).…”
mentioning
confidence: 99%